If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -5x + 9 = 25 Reorder the terms: 3 + 9 + -5x = 25 Combine like terms: 3 + 9 = 12 12 + -5x = 25 Solving 12 + -5x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -5x = 25 + -12 Combine like terms: 12 + -12 = 0 0 + -5x = 25 + -12 -5x = 25 + -12 Combine like terms: 25 + -12 = 13 -5x = 13 Divide each side by '-5'. x = -2.6 Simplifying x = -2.6
| f(x)=5x^2+bx+c | | f(x)=-7x^2+28x+25 | | 6x=27y-3 | | (6*6)*(4*4*4)= | | 5(X-13)-7(6-X)+29=50-3(8-X) | | a+(a-8)=44 | | %.317=164 | | x^2+6.91830971e-7x-4e-8=0 | | x^2-3x/7x | | p+(-4)=1 | | 1a(105/(35/7)) | | 8x+8=9x-7 | | 3x+2x-5=x+7 | | 1/4×16 | | x^2+x-0.058=0 | | 48/165 | | 1/3(9x-12)=1/4(16x-12) | | 2x-5=3x-16 | | X/22=15/33 | | x+(x+1)+(x+2)=(x+3)+100 | | x+(x+1)+(x+2)=100 | | x-4=-x+6 | | 12/x=3/10 | | 3(7+10)+4(7+20)+5(7)=185-3(7) | | 2/6=6/x | | 4x+9=-4x+17 | | 3(7+10)+4(7+20)+5(x)=185-3(7) | | x+(x+2)+(x+3)=100 | | x^2-3/7 | | 6/c | | 5x+6=-3x+22 | | 3x-8=-6x+19 |